Characteristics associated with the type of donor in kidney transplant; an experience in a high-altitude city - Giuston Mendoza-Chuctaya; Carla Liñán-Mejía; Kevin Rodrigo Ramos Chuctaya; Christian R. Mejia; Jorge Ruiz-Esquivel (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Renal transplantation has been mainly studied in coastal cities or low-altitude areas, which is a significant limitation of the field. Objectives: The objective of this study was to determine the survival rates, and characteristics associated with the type of donor, in patients with renal transplantation at a high-altitude Peruvian hospital. Patients and Methods: We performed a retrospective cohort study of 63 transplanted patients in Cusco, Peru. Depending on the type of donor (living or cadaveric), associations were found according to sociocultural characteristics of the donor and recipient, and according to physio-anthropometry and characteristics of the disease. It was used analytical statistics. Results: Fifty-one percent (32) of kidney transplants came from a cadaveric donor. Statistically significant differences were found according to the kinship of the donor (P<0.001), recipient age (P=0.042), cold ischemia time (P<0.001), and blood urea value (P=0.008). A year after the transplant, there was a 98% patient survival rate (CI: 89-100%) and a 97% graft survival rate (CI: 87-99%). Ten years later, the survival rate was 92% for patients (CI: 75-98%) and 53% for grafts (CI: 33-70%); there were no differences in patient survival (P=0.654) or graft survival (P=0.851) between donor types. Conclusion: The results indicate that in a high-altitude population study, survival rate is slightly higher than in studies performed at sea level, and this does not depend on donor type (living or cadaveric). In addition, statistically significant differences in survival rates were found depending on the kinship of the donor, recipient age, and cold ischemia time.